2006
DOI: 10.1177/039463200601900218
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Histopathological and Molecular Changes of Small B-Cell Lymphomas after Rituximab Therapy: Comparison with Clinical Response and Patients' Outcome

Abstract: This study correlates bone marrow changes after Rituximab (RTX) treatment with the clinical characteristics and outcome of 26 patients with small B-cell lymphomas. The percentage, phenotypic profile and clonality pattern of bone marrow lymphoid infiltrate were analysed before and after RTX treatment. Clinical, histological and molecular responses to RTX were correlated to the clinical outcome of the patients. Sixteen out of twenty-six patients obtained a complete clinical remission (CR). A favourable histology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
(24 reference statements)
0
19
0
Order By: Relevance
“…However, distinguishing MCL with PC differentiation from MCL with a concurrent but unrelated plasma cell dyscrasia may have treatment implications. Furthermore, other B-cell lymphomas with PC differentiation have been reported to show post-treatment relapses with only PC histology (19,20). The distinctive phenotype of the plasma cells in this case, with coexpression of CD5 and CD19, renders flow cytometry immunophenotyping of great value in evaluating possible relapses that show only PC histology.…”
Section: Discussionmentioning
confidence: 78%
“…However, distinguishing MCL with PC differentiation from MCL with a concurrent but unrelated plasma cell dyscrasia may have treatment implications. Furthermore, other B-cell lymphomas with PC differentiation have been reported to show post-treatment relapses with only PC histology (19,20). The distinctive phenotype of the plasma cells in this case, with coexpression of CD5 and CD19, renders flow cytometry immunophenotyping of great value in evaluating possible relapses that show only PC histology.…”
Section: Discussionmentioning
confidence: 78%
“…It was also shown that NK cells from non-immune individuals can kill plasmodia-infected erythrocytes in the absence of opsonizing antibodies directly through cell-cell interaction, and that this activity was inhibited by anti-FAS antibody and granzyme B inhibitor (55). Furthermore, the finding of children with acute P. falciparum infection suggested a positive correlation between the lytic activity of natural killer cells towards the human leukemia line k562 ex vivo and the extent of parasitemia, and provided evidence that purified NK cells from both healthy and P. falciparum-infected individuals directly lyse parasitized erythrocytes in vitro (56)(57)(58)(59)(60)(61)(62). This optimal activation of NKderived IFN-γ production in vitro requires contact between NK cells and P. falciparum-infected erythrocytes (53).…”
Section: Nk Cells and Parasitesmentioning
confidence: 99%
“…Furthermore, the bone marrow neoplastic cells were positive for CD5, CD19 ( Figure 3C), CD23, CD25, and λ-chain of immunoglobulin light chain and negative for not only CD3 and CD10, but also for CD20 ( Figure 3D), which was found to be positive at the initial diagnosis ( Figure 3B) by the cell surface marker analysis using flow cytometry. Complicated chromosomal abnormalities including abnormalities in chromosomes 3,6,7,8,9,13,15,16,17, and 19, were detected in 15 of 20 analyzed BMCs by the G-banding method. The abnormalities in chromosome 11, which were detected at the initial diagnosis, were not included.…”
Section: Introductionmentioning
confidence: 99%
“…We ultimately concluded that the neoplastic B-CLL/SLL cells lost the expression of the CD20 antigen after the rituximab treatment. a small number of cases have been reported thus far [9,[12][13][14][15]. The characteristics of 11 patients (including 6 males) whose details were described are listed in Table 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation